2008
DOI: 10.1172/jci35017
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic leukemia T cells show impaired immunological synapse formation that can be reversed with an immunomodulating drug

Abstract: Cancer is associated with immune deficiency, but the biologic basis of this is poorly defined. Here we demonstrate that impaired actin polymerization results in CD4 + and CD8 + T cells from patients with chronic lymphocytic leukemia (CLL) exhibiting defective immunological synapse formation with APCs. Although this synapse dysfunction was in part a result of the CLL cells having poor APC function, defective actin polymerization was also identified in T cells from patients with CLL. We further demonstrate that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
542
5
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 392 publications
(590 citation statements)
references
References 45 publications
12
542
5
12
Order By: Relevance
“…Using these samples, we clearly demonstrated that LN-CLL cells had enhanced expression of markers that would induce T-cell activation. In contrast to previous studies, which suggest that PB-CLL cells are poor APCs, 22,27 induce T-cell anergy, and inhibit T-cell activation, 20,21,28 we showed that LN-CLL cells can induce T-cell activation and proliferation. We also showed that, in contrast to PB-CLL cells, those from the LN were capable of forming immune synapses with autologous CD4 1 T cells that were comparable to those formed by healthy B and T cells.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Using these samples, we clearly demonstrated that LN-CLL cells had enhanced expression of markers that would induce T-cell activation. In contrast to previous studies, which suggest that PB-CLL cells are poor APCs, 22,27 induce T-cell anergy, and inhibit T-cell activation, 20,21,28 we showed that LN-CLL cells can induce T-cell activation and proliferation. We also showed that, in contrast to PB-CLL cells, those from the LN were capable of forming immune synapses with autologous CD4 1 T cells that were comparable to those formed by healthy B and T cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous work has shown that PB-CLL cells exhibit impaired T-cell synapse formation. 20 Here, we measured synapse assembly (CLL:CD4 1 T-cell conjugates) in 4 patient samples and demonstrated for the first time that LN-CLL cells showed enhanced autologous T-cell synapse formation, equivalent to that induced by healthy B cells, 24 BLOOD, 28 JULY 2016 x VOLUME 128, NUMBER 4…”
Section: Enhanced Capacity Of Ln-derived Cll Cells To Activate T Cellsmentioning
confidence: 88%
See 1 more Smart Citation
“…6 Indeed, T-cell abnormalities occurring alongside CLL have been observed for a long time 7,8 and, more recently, an aberrant interaction between T cells and CLL cells has been described. 9 Our own previous work suggested that in human CLL the T-cell subset composition is severely skewed and that this was associated with stage, progressive disease, and time to development of a treatment indication. 10 These data suggested that an accumulation of antigen-experienced T cells in the memory compartment were somehow associated with a more aggressive disease course.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms whereby this occurs are poorly understood, but include direct cancer cell-T cell interactions, production of immune-suppressive factors by cancer cells, and induction of regulatory T-cell subsets (1,2). Understanding the elusive mechanisms of tumor-driven immune evasion will aid the refinement of existing cancer immunotherapy strategies and identify novel treatments.…”
mentioning
confidence: 99%